Antimicrobial Peptides: a New Frontier in Antifungal Therapy - Buda De Cesare, Giuseppe; Cristy, Shane A.; Garsin, Danielle A.; Lorenz, Michael C. (mBio, 2020)
Invasive fungal infections in humans are generally associated with high mortality, making the choice of antifungal drug crucial for the outcome of the patient. The limited spectrum of antifungals available and the development of drug resistance represent the main concerns for the current antifungal treatments, requiring alternative strategies. Antimicrobial peptides (AMPs), expressed in several organisms and used as first-line defenses against microbial infections, have emerged as potential candidates for developing new antifungal therapies, characterized by negligible host toxicity and low resistance rates. Invasive fungal infections in humans are generally associated with high mortality, making the choice of antifungal drug crucial for the outcome of the patient. The limited spectrum of antifungals available and the development of drug resistance represent the main concerns for the current antifungal treatments, requiring alternative strategies. Antimicrobial peptides (AMPs), expressed in several organisms and used as first-line defenses against microbial infections, have emerged as potential candidates for developing new antifungal therapies, characterized by negligible host toxicity and low resistance rates. Most of the current literature focuses on peptides with antibacterial activity, but there are fewer studies of their antifungal properties. This review focuses on AMPs with antifungal effects, including their in vitro and in vivo activities, with the biological repercussions on the fungal cells, when known. The classification of the peptides is based on their mode of action: although the majority of AMPs exert their activity through the interaction with membranes, other mechanisms have been identified, including cell wall inhibition and nucleic acid binding. In addition, antifungal compounds with unknown modes of action are also described. The elucidation of such mechanisms can be useful to identify novel drug targets and, possibly, to serve as the templates for the synthesis of new antimicrobial compounds with increased activity and reduced host toxicity.